PEMBERDAYAAN PENDIDIKAN ISLAM SEBAGAI UPAYA PENGENTASAN KEMISKINAN - H. Moh Armoyu (IAIN Ponorogo, 2013)
Abstract: The problem of poverty has happened for long times and it seems to be more complicated and endless matter. Because of poverty, many children cannot proceed to study and even they should work to help parents earn for living. Therefore, it needs high effort and commitment to overcome this problem and it should be done deliberately and continuously. This study attempted to investigate the role of education in poverty alleviation in Indonesia. The data was collected by employing in-depth interviews and analyzed using phenomenological models. The results showed that: ( 1 ) the level of education could cut the chain of poverty; ( 2 ) in general, the results of this study found that there were a foster care program for children from economically-challenged families, educational empowerment that emphasizes children from economically-challenged families as a central point of empowerment in the development process, and providing opportunity for talented children from economically-challenged families to proceed higher study in reputable universities, (3) conducting research to select students who will be given a scholarship, based on academic experience and the background of parents. في دلاولأا نم يرثك سردي لا رقفلا بسسب .ةياهنلا اله سيل نأكو دهعلا ةيمدق ةيضق رقفلا ةيضق :صخلم لصاوتلما يعاملجا مزعلا دوجو نم دبلا اذل .شاعلما ىلع لوصحلل )نولمعي( مهءابآ نودعاسي لب سرادلما ميدقت في مهسيل رقفلا ةيضق ىلع ءاضقلا في ةيبترلا رود في ثحبلا ةساردلا هذه تلواح .ةلكشلما هذه للح ةلباقلما قيرط نع اهتانايب عمتجو ايسينودنإ في ثحبلا اذه يرحأ .ةيبترلا قيرط نع رقفلا ةيضقل للحا لبس يوبترلا ىوتسلما نأ )1 : ىلع ثحبلا جئاتن تلد . يجولونمونيفلا ليلحتلاب هليلتح بولسأ امأو ،ةقيمعلا ةساردلا نع ينعطقنلما دلاولأا ينضتح جمانرب كانه نأ ىلع ةساردلا تلد ةماعو )2 ،رقفلا ةلسلسل عطاق مايقلا )3 ،ةييمداكلأا مهتاردق ةيمنتل ةمدقتلما تاعمالجا وأ سرادلما في ملهاخدلإ ةلوالمحاو ةيرقفلا رسلأا نم مهئابآ ةيفلخو ةييمداكلأا مهابرخ بسح ةيساردلا ةحنلما ىلع نولصحيس نيذلا بلاطلا هاتج قيقد ليلحتب مهتاهمأوKeywords: Pemberdayaan, pengentasan kemiskinan, pendidikan Islam.